Solvent extraction separation of copper and zinc from MSWI fly ash leachates. (October 2015) - Tang, Jinfeng; Steenari, Britt-Marie
Highlights: A leaching and solvent extraction process for Cu and Zn recovery from municipal solid waste combustion fly ash was developed. Cu yields of 69–87% and Zn yields of 75–80% were obtained in laboratory scale experiments. Co-extraction of Fe, Pb, and Cd with Zn can be avoided by cementation before the Zn extraction. Abstract: Fly ash from combustion of municipal solid waste (MSW) contains significant amounts of metals, some of which are valuable and some of which are potentially toxic. This type of ash is most often stabilized and landfilled which means that the metals will be difficult to reclaim at a later stage. In recent years efforts have been made to develop feasible methods to recover selected metals, such as Zn, from MSW fly ash. If this would be possible, a significant amount of valuable metals could be re-inserted in the industrial material loops. This paper describes the development and evaluation of a process for recovery of Cu and Zn from MSW combustion fly ash based on hydrochloric acid leaching followed by two solvent extraction processes, one for each metal. The separation of Cu from the acid leachate was done using an aldoxime extractant, LIX860N-I, in kerosene and a mixture of phosphine oxides, Cyanex 923, also in kerosene, was used for extraction of Zn from the Cu-depleted aqueous phase. The extraction of Cu was selective, but a significant amount of other metals, such as Fe and Pb, were co-extracted together with Zn. It was shown that it is possible to decrease the contamination of Fe by using a suitable concentration of nitric acid solution for stripping or by removing the contaminating metals through cementation. The suggested process was tested for two MSW combustion fly ashes in laboratory scale experiments and gave Cu yields of 69–87% and Zn yields of 75–80% based on the contents in the ash.